The Impact of Lifting Stay-at-Home Orders on Local Unemployment Rates in the United States During COVID-19 Using Arizona and California as comparison - Shen Shijun (SHS Web of Conferences)
Facing the pandemic, the local governments of the United States have implemented different measures against the spread of COVID-19. These measures severely hit the labour market. The paper focuses on the effect of lifting the stay-at-home Order on the region-level unemployment rate. Two neighbouring states, Arizona and California are chosen as the treatment group and the control group. The paper used the DID method to study the policy’s impact on the unemployment rate given that Arizona and California had different opening timelines. Three models with different specifications are developed. The result shows that lifting of the stay-at-home Order has significantly reduced the unemployment rate in the regions in Arizona by 1.962 percent. The result also shows the heterogeneity of the treatment effects across time. The policy’s influence gradually increased in the first 3 months and faded away after the first 16 months. The paper then provided possible explanations for such observations.